A Novel Kite-Shaped Chipless RFID Tag for Low-Profile Applications. Issue 3 (4th May 2022) - Tariq, Nimra; Riaz, Muhammad Ali; Shahid, Humayun; Khan, Muhammad Jamil; Amin, Yasar; Tenhunen, Hannu
Abstract : In this paper a novel, compact 10-bit chipless radio frequency identification (RFID) tag with stable readable characteristics is proposed. The tag is composed of several concentric novel kite-shaped loop resonators. The desired data sequence is obtained by the insertion or removal of nested elements, offering a 1:1 data bit to resonance correspondence. Each data sequence is encoded in the spectral domain of the tag. The proposed tag shows operability at different polarizations and incident angles of the impinging electromagnetic waves. Operating within the ultra-wideband (UWB), the tag is realized on the Roger RT/duroid ® 5880 substrate having physical dimensions of 13.55 × 13.55 mm 2 . The measurement results of the design reveal a high code density and spectral efficiency of 5.44 bits/cm 2 and 2 bits/GHz, respectively. The compact and robust passive chipless RFID tag having scalable data storage potential can be deployed in numerous low-profile applications such as those of wearable and healthcare.